Effect of nano-calcium carbonate on resistance to calcium leaching and chloride penetration in recycled concrete - Jian-Hua Jiang; Si-Qi Zhao; Xiao-Zhe Shi; Rui-Qi Xia; Huang-Xin Zhang (European Journal of Environmental and Civil Engineering, 2026)

Metabolic complementarity and enhanced biofilm formation drive the synergistic symbiosis of lactic acid bacteria and yeast in Tibetan kefir - Liangli Wu; Jianwei Zang; Luyao Xiao; Chang Xu; Xia Fan; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Tao Lin; Wei Li (International Dairy Journal, 2026)

Evolution of lipid profiles, microbiota succession, and potential warmed-over flavor markers in prepared squid (Dosidicus gigas) during extended refrigerated storage: A multi-omics study - Xin Zhang; Rui Tan; Chengxin Lv; Zhiyuan Xiao; Kang Guo; Bin Zhang; Ru Song; Yan Xu; Wei Xia (Food Bioscience, 2026)

Fermentation of ginseng juice by Lactiplantibacillus plantarum SP055 and Limosilactobacillus fermentum LB-9: Fermentation characteristics and ginsenoside biotransformation pathways - Jianwei Zang; Wei Liu; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Yimeng Kou; Chunling Meng; Jiamin Xu; Tao Lin; Xin Rui; Dan Gan; et al. (Food Microbiology, 2026)

Tailoring polyhydroxybutyrate by molecular weight regulation: Green synthesis, food-grade performance and innovative ketogenic applications - Jin Hui Xie; Jia Ying Xin; Yan Wang; Li Rui Sun; Hai Xin Bi; Jian Xiong Zhang; Chun Gu Xia (Food Research International, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

Inhalable HUCMSC-Lipo biomimetic formulation inhibits fibroblast activation in mouse and non-human primate pulmonary fibrosis models - Fangyu Zhao; Yige Sun; Haoran Wang; Dayong Hou; Rui Zhang; Wenjing Xia; Yongchen Zhang; Luyao Li; Xueqi Zhao; Kaiqi Wang; Wenwen Pan; Jiannan Wang; et al. (Science Bulletin, 2026)

Balancing the modulation of soy protein structure to achieve improved texture and reduced antigenicity in soy yogurt: A practical approach of proteolytic pretreatment and lactic acid bacteria fermentation - Qiyuan Lu; Xinran Guo; Xia Fan; Benjamin K. Simpson; Wei Li; Xin Rui (Food Chemistry, 2026)

Lactiplantibacillus plantarum SP055 pretreatment attenuates experimental colitis in association with partial preservation of epithelial integrity and microbial-metabolic homeostasis - Jianwei Zang; Xiaotong Hao; Yibo Shi; Xia Fan; Yimeng Kou; Xiaogan Zhao; Qiaoya Mo; Di Yu; Jiamin Xu; Chunling Meng; Chang Xu; Luyao Xiao; et al. (Food Bioscience, 2026)

Acute Stress Drives Adaptive Anxiety via Excitatory-Inhibitory Imbalance in the Prefrontal-Amygdala Circuit in Male Mice - Jia-Xin Zou; En Cao; Zhi-Hao Wang; Rui Han; Xing-Yan Lu; Cheng-Yuan Huang; Xia Qin; Wei-Zhu Liu; Wen-Hua Zhang; Bing-Xing Pan (Neuroscience Bulletin, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Tropical-origin lactic acid bacteria co-fermentation enables protein network restructuring and glucose-lipid metabolic regulation in coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Xia Fan; Xin Rui; Tao Lin; Wei Li (Innovative Food Science & Emerging Technologies, 2026)

Lipid-driven modulation of milk/soy proteins digestion in young child formulas: From in vitro gastric emptying to intestinal absorption coupled with in vivo protease activation - Qiaoya Mo; Jiahui Wang; Chang Xu; Xia Fan; Tao Lin; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Research International, 2026)

A near-infrared AIEgens-based fluorescent probe with large stokes shift for selective lysine detection: Photophysical properties, chirality transmission, and bioimaging applications - Xin Wang; Wenhui Xue; Penghui Xia; Qian Wang; Shizhen Wang; Yuefeng Zhu; Nuo Fei; Keting Zhu; Yuhan Li; Ruimeng Ye; Yang Liu; Zhixin Dong; et al. (Food Chemistry, 2026)

A tropical fermented-food-derived Lactiplantibacillus plantarum SP055 alleviates DSS-induced colitis through coordinated regulation of gut microbiota and intestinal barrier function - Jianwei Zang; Yibo Shi; Xiaotong Hao; Xia Fan; Yimeng Kou; Wanxiang Zhang; Luyao Xiao; Chang Xu; Tao Lin; Xin Rui; Dan Gan; Wei Li (Food Bioscience, 2026)

From addition to regulation: Lactic acid bacteria-driven interfacial mechanisms and spatial control in food bioactive packaging - Jianwei Zang; Yan Luo; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Luyao Xiao; Xin Rui; et al. (Trends in Food Science & Technology, 2026)

Gallic acid-modified starch conjugates inhibit harmful aldehydes in fried battered fish: Based on structural characterization and antioxidant activity - Ying Li; Hao Zhang; Jiamu Kang; Meng Yang; Hanyu Liu; Wuyun Chen; Tingting Zhang; Deming Quan; Rui Zhang; Yuan Xia; Xin Du; Xiufang Xia (Food Research International, 2026)

Co-fermentation with autochthonous Levilactobacillus brevis and Lactiplantibacillus plantarum modulates metabolome and volatile profiles to improve the quality and safety of fermented chopped chili - Wenkai Jiang; Qian Yang; Luyao Xiao; Xia Fan; Menghan Zhong; Mahsa Ghahvechi Chaeipeima; Kai Ma; Changliang Zhang; Xin Rui; Wei Li (Food Research International, 2026)

Strain-specific effects of infant-derived Bifidobacterium on gut microbiota modulation and mucus barrier responses in Salmonella infection - Xiaogan Zhao; Mahsa Ghahvechi Chaeipeima; Luyao Xiao; Xia Fan; Wenkai Jiang; Xiran Jia; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Bioscience, 2026)

A multi-stimuli-responsive supramolecular polymer from γ-Cyclodextrin and Viologen for dual-mode display and ammonia/amines sensing - Dong-Xue Xia; Chen-Yan Xu; Dan-Xuan Pan; Ming-Fu Ye; Rui-Lian Lin; Jing-Xin Liu (Chemical Engineering Journal, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Inhibitory effects of various lignocellulose pretreatment byproducts on xylonic acid biosynthesis by Gluconobacter oxydans - Fan Li; Shuiping Ouyang; Rui Zhang; Xia Hua; Yong Xu; Xin Zhou (Bioresource Technology, 2026)

Small-sized fixed domain monitoring underwater profiler: A multi-factor comparative analysis - Yang Zhang; Xin Zhang; Qingchao Xia; Canjun Yang; Ruiyin Song; Dingze Wu; Rui Zhou; Jiayu Hou; Gul Muhammad (Ocean Engineering, 2025)

Xylo-oligosaccharide utilization by Weissella kandleri YT103: Transcriptomic analysis and intestinal barrier protection - Xin-rui Zhang; Shuang-shuang Cui; Long-fen Yin; Gui-zhen Gong; Jian-xia Yang; Yang Chen; Yuan-ting Zhu (Food Research International, 2025)

Fabrication and characterization of starch-based edible films loaded with Lactiplantibacillus plantarum STB9b for pork preservation - Jianwei Zang; Yue Hu; Tao Lin; Xia Fan; Yimeng Kou; Yibo Shi; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Wei Li (Food Packaging and Shelf Life, 2025)

Transcriptomic analysis of the mechanism of male reproductive injuries caused by the mixture of three phthalates in rats - Ling-Zi Xia; Jun-Zhe Yue; Li-Jun Wu; Qian-Ying Jin; Yi-Pei Yang; Jing-Yang Yu; Rui-Zhe Pan; Xin Zhang; Xiao-Ying Wu; Jiayin Zhu; Hai-Tao Gao (Toxicology and Applied Pharmacology, 2025)

Assessment of the effects of oligosaccharide supplementation on the structure of lactic-fermented soy protein gel and its allergenic epitopes - Xinran Guo; Xiaocui Lu; Di Yu; Xia Fan; Wei Li; Xin Rui (Food Hydrocolloids, 2025)

Vapor additive strategy enabling perfect crystallization of vacuum-evaporated photovoltaic perovskites - Lei Huang; Zhang Chen; Kai-Li Wang; Zi-Hao Song; Xiao-Ying He; Zhen-Huang Su; Jing Chen; Chun-Hao Chen; Yu Xia; Yu-Tong Yang; Xin Chen; Rui-Hao Qin; et al. (Chemical Engineering Journal, 2025)

Jingfang granule extends lifespan and healthspan in Caenorhabditis elegans: insights from RNA-seq analysis of genetic mechanisms - Taili Zhao; Yunhua Hou; Chuanjiao Feng; Rui Zhao; Honghua Li; Peipei Zhao; Mengmeng Wang; Jingli Ren; Yiwei Meng; Kuidong Xu; Jia Liu; Xin Yin; et al. (Biogerontology, 2025)

Elucidating the anti-aging bioactive compounds and mechanisms of Jingfang Granules formula based on network pharmacology and Caenorhabditis elegans - Rui Zhao; Taili Zhao; Tingting Shi; Chuanjiao Feng; Honghua Li; Ying Xu; Qingqing Zhang; Xin Yin; Jingchun Yao; Guimin Zhang; Xuekui Xia (Biogerontology, 2025)

Climate change, social environment, health, and urban inequality: Developing a novel adaptive evaluation framework - Nan Jia; Yinshuai Li; Zhimeng Jiang; Rongfei Su; Xin Lan; Kai Zhang; Wen Song; Rui Zhao; Zilong Xia; Yongze Song; Zehua Zhang; Mengting Wang; et al. (Sustainable Cities and Society, 2025)

Assessing the potential for a novel Composite Integrative Passive Sampler (CIPS) to investigate transboundary movement of organic chemicals in the Tijuana River Estuary - Zuying Feng; Flannery McLamb; Damian Shea; Kesten Bozinovic; Chris Stransky; Richard M. Gersberg; Wenling Wang; Xiang Kong; Xin-Rui Xia; Miguel F. Vasquez; MacKenzie King; Goran Bozinovic (Science of The Total Environment, 2025)

Research on the dynamical behavior of air-dropped underwater profiler and virtual mooring strategy for variable pitch angle - Dingze Wu; Rui Zhou; Qingchao Xia; Puzhe Zhou; Xin Zhang; Zhilan Jin; Yang Zhang; Canjun Yang (Ocean Engineering, 2025)

SfM on-the-fly: A robust near real-time SfM for spatiotemporally disordered high-resolution imagery from multiple agents - Zongqian Zhan; Yifei Yu; Rui Xia; Wentian Gan; Hong Xie; Giulio Perda; Luca Morelli; Fabio Remondino; Xin Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Bimetallic organic framework-derived multifunctional signal marker-driven ultra-magnetic nanoplatform for sensitive detection and efficient sterilization of methicillin-resistant Staphylococcus aureus - Xin Zhang; Xiaoyu Yu; Yuwei Ren; Rui Jiao; Hui Li; Xiyan Zhang; Ganghui Li; Xiyang Xia; Na Ling; Danfeng Zhang; Yingwang Ye (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Salinicoccus bachuensis sp. nov., a novel halophilic bacterium, isolated from rhizosphere soil surrounding Tamarix chinensis Lour. plants in Bachu County, Xinjiang, China - Zhen-Pu Liang; Rui Wang; Han-Wen Cao; Xin-Lu Zhou; Jin-Ping Dai; Ping Su; Deepali Singh; Xiao-Xia Zhang (Archives of Microbiology, 2025)

Magnetic graphene-enhanced exonuclease III assisted amplification strategy driven carbon nanozyme for tri-mode detection of Escherichia coli O157:H7 - Yuwei Ren; Lulu Cao; Zongyang Li; Xin Zhang; Hui Li; Rui Jiao; Xiaoyu Yu; Zhao Liang; Ganghui Li; Xiyang Xia; Na Ling; Danfeng Zhang; et al. (Food Chemistry, 2025)

Numerical and experimental studies on the hydrodynamic performance of a composite cylindrical perforated-wall caisson breakwater - Zi-bo Xia; Xin-yu Wang; Xiao Liu; Rui-jia Jin; Bao-lei Geng; Yong Liu (Ocean Engineering, 2025)

Adhesive conductive wood-based hydrogel with high tensile strength as a flexible sensor - Rui Yang; Xiaoqi Yang; Linghui Qi; Xiangzhen Meng; Lili Dai; Xin Jin; Jing Zhou; Haiyang Lu; Changlei Xia; Jianzhang Li (Carbohydrate Polymers, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Evaluating pulmonary toxicity of PFOS and its alternative OBS using spheroids of A549 cells - Chong-Rui Yao; Yu-Xia Jiang; Si-Ying Li; Zhi-Jie Lu; Xiao-Bing Long; Na Xin; Jin-Ge Zhang; Dong-Dong Ma; Guang-Guo Ying; Wen-Jun Shi (Science of The Total Environment, 2024)

The Influence of pH on Sulfamethoxazole in Soil Systems: Migration and Degradation - Haifang Wang; Xin Li; Zhumei Sun; Xia Cao; Junli Zhang; Qihua Chen; Rui Ma (Water, Air, & Soil Pollution, 2024)

The Roles of RNA N6-methyladenosine Modifications in Systemic Lupus Erythematosus - Xin Xia; Rui Qu (Cell Biochemistry and Biophysics, 2024)

Optimizing waste leachate treatment for environmental and economic sustainability: Insights from a bottom-up study of over 300 cities - Qian-long Han; Hai-long Zhao; Guo-xia Wei; Han-qiao Liu; Yu-wen Zhu; Tong Li; Yan-fei Lin; Xin-rui Su (Sustainable Production and Consumption, 2024)

Stochastic process is main factor to affect plateau river fish community assembly - Xiaoxuan Li; Qigong Xu; Rui Xia; Nan Zhang; Shuping Wang; Sen Ding; Xin Gao; Xiaobo Jia; Guangxia Shang; Xiaofei Chen (Environmental Research, 2024)

Computational tools for plant genomics and breeding - Hai Wang; Mengjiao Chen; Xin Wei; Rui Xia; Dong Pei; Xuehui Huang; Bin Han (Science China Life Sciences, 2024)

Dual-Mode Square Root Cubature Kalman Filter for Miniaturized Underwater Profiler Dead Reckoning - Yang Zhang; Qingchao Xia; Canjun Yang; Ruiyin Song; Dingze Wu; Xin Zhang; Rui Zhou; Shuyang Ma (Journal of Marine Science and Engineering, 2024)
Miniaturized underwater profilers have the advantages of small size, low cost, and flexible deployment, which play together an important role in the persistent monitoring of a designated ocean area. Based on the demand for ocean observation, the system design, dynamic modeling, and dead reckoning algorithm of a miniaturized underwater profiler are carried out. The process of the persistent monitoring of designated area with a miniaturized underwater profiler is analyzed, and the overall structure of the miniaturized underwater profiler was designed. Additionally, the kinematic and dynamic model of the miniaturized underwater profiler is given based on the inertial and body coordinate systems. Then, according to the state equation and the observation equation of the miniaturized underwater profiler, a dual-mode square root cubature Kalman filter (DSRCKF) algorithm, combining standard SRCKF and adaptive SRCKF, is proposed for the dead reckoning of the miniaturized underwater profiler. Finally, a comprehensive comparison of EKF, UKF, CKF, SRCKF, and DSRCKF and the associated simulations and experiments are conducted to verify the performance of the underwater dead reckoning algorithm for the miniaturized underwater profiler. The results show that the DSRCKF algorithm has a certain role in the dead reckoning of the miniaturized underwater profiler, particularly in the z direction and attitude. In future, a real underwater dead reckoning test using miniaturized underwater profiler will be carried out.

Lotus pollen-derived nitrogen and phosphorus self-doped TiO2/carbon materials for photoelectrochemical application - Rui Chen; Ying-Ying Wang; Xia Jiang; Ming-Hao Ji; Ke-Xian Li; Hao-Yan Shi; Hai-Long Wang; Yan-Xin Chen; Can-Zhong Lu (Journal of Environmental Chemical Engineering, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Self-assembly of metal-polyphenolic network on biomass for enhanced organic contaminant capturing from water with a high cost-to-benefit ratio - Xin Jin; Xueyi Li; Yubo Liu; Yilong Cui; Yunyi Liang; Qin Wang; Jin Wang; Rui Yang; Jianwei Zhao; Changlei Xia (Journal of Hazardous Materials, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Leaching and evolution of anthocyanins and aroma compounds during Cabernet Sauvignon wine fermentation with whole-process skin-seed contact - Xue-Chen Yao; Hua-Lin Zhang; Xin-Rui Ma; Nong-Yu Xia; Chang-Qing Duan; Wei-Ming Yang; Qiu-Hong Pan (Food Chemistry, 2024)

Chameleon-inspired supramolecular materials based on cucurbit[7]uril and viologens exhibiting full-color tunable photochromic behavior - Dong-Xue Xia; Xin Wang; Wen-Qi Sun; Rui-Lian Lin; Jing-Xin Liu; Ying-Wei Yang (Chemical Engineering Journal, 2024)

Structurally diverse rearranged sesquiterpenoids, including a pair of rare tautomers, from the aerial parts of Daphne penicillata - Peng Zhao; Ben-Song Xin; Li Ye; Zhen-Tao Ma; Guo-Dong Yao; Rui Shi; Xia-Hong He; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Risk assessment and source identification of soil heavy metals: a case study of farmland soil along a river in the southeast of a mining area in Southwest China - Huajian Chi; Xin Liu; Xiaofang Yang; Rui Zhang; Ting Xia; Yiping Sun; Kan Hu; Fangfang Hao; Yong Liu; Shengchun Yang; Qingwen Deng; Xiaodong Wen (Environmental Geochemistry and Health, 2024)

Evidence of transboundary movement of chemicals from Mexico to the U.S. in Tijuana River Estuary sediments - Flannery McLamb; Zuying Feng; Damian Shea; Kesten Bozinovic; Miguel F. Vasquez; Chris Stransky; Richard M. Gersberg; Wenling Wang; Xiang Kong; Xin-Rui Xia; Goran Bozinovic (Chemosphere, 2024)

17β-Estradiol Mediates Staphylococcus aureus Adhesion in Vaginal Epithelial Cells via Estrogen Receptor α-Associated Signaling Pathway - Lina Yan; Can Rui; Bin Zhuang; Xia Liu; Ting Luan; Lisha Jiang; Zhiyong Dong; Qing Wang; Aiwen Wu; Ping Li; Xinyan Wang; Xin Zeng (Current Microbiology, 2023)

Triazole fungicides exert neural differentiation alteration through H3K27me3 modifications: In vitro and in silico study - Tingting Ku; Xin Tan; Yutong Liu; Rui Wang; Lifan Fan; Zhihua Ren; Xia Ning; Guangke Li; Nan Sang (Journal of Hazardous Materials, 2023)

Bimodal interferences of Pb(II) induced by parallel deposition in Pb(II)-Cu(II) electrochemical detections: Voltammetric signals analysis combined with numerical simulations on transient interfacial phenomena - Rui-Ze Xia; Xin Cai; Bo Liang; Hai-Hua Dai; Yang-Zhi Liu; Meng Yang; Shi-Hua Chen; Pei-Hua Li; Xing-Jiu Huang (Journal of Hazardous Materials, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Distinguishing the contributions of hot holes from interband and intraband transitions to the photoenhanced electrocatalytic oxidation reaction of ethanol - Chen Chi; Miao Ni; Xin-Lei Ding; Dong-Rui Yang; Jian Li; Xing-Hua Xia (Science Bulletin, 2023)

SnS2-covalent organic framework Z-scheme van der Waals heterojunction for enhanced photocatalytic reduction of uranium (VI) in rare earth tailings wastewater - Xin Liu; Rui-Xiang Bi; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Balance the rapid release of insecticide microcapsules using double-layer shielding effect when the foliar application - Rui Wang; Song Liu; Feng-shou Sun; Xin Yu; Xiao Liu; Bei-xing Li; Wei Mu; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2023)

Receptor and Ionic Mechanism of Histamine on Mouse Dorsolateral Striatal Neurons - Jian-Ya Peng; Kang-Li Shen; Xiu-Juan Fan; Zeng-Xin Qi; Hui-Wei Huang; Jian-Lan Jiang; Jian-Hua Lu; Xiao-Qin Wang; Xiao-Xia Fang; Wang-Rui Yuan; Qiao-Xuan Deng; Shu Chen; et al. (Molecular Neurobiology, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

Somatic embryogenesis of masson pine (Pinus massoniana): initiation, maturation and genetic stability analysis at SSR loci - Xin-Rui Xia; Fan Yang; Xin Ke; You-Mei Chen; Jian-Ren Ye; Li-Hua Zhu (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Antifungal Effect of Long Noncoding RNA 9708-1 in the Vulvovaginal Candidiasis Murine Model - Ying Wu; Lisha Jiang; Lingling Zhang; Xia Liu; Lina Yan; Ting Luan; Can Rui; Zhiyuan Mao; Chong Fan; Yu Liu; Ping Li; Xin Zeng (Mycopathologia, 2021)
Vulvovaginal candidiasis (VVC) caused by Candida spp. affects 70–75% of women at least once during their lives. We aim to elucidate the potential mechanism of VVC and investigate the therapeutic effects of long noncoding RNA 9708-1. Female BALB/c mice were randomized to four treatment groups, including the blank control group, VVC control group, vehicle control group and lncRNA 9708-1-overexpressed group. Mice were euthanized on Day 4, Day 7 and Day 14 after treatment. Colony-forming unit (CFU) was measured, and the inflammation was detected by hematoxylin and eosin (H&E). Gene and protein expression levels of lncRNA 9708-1 and FAK were determined by real-time PCR, Western blot and immunohistochemistry. The overexpression of lncRNA 9708-1 significantly decreased the fungal load from Day 4 to 7. H&E staining indicated that the impaired histological profiles were improved in lncRNA 9708-1-overexpressed group. LncRNA 9708-1 led to a significant increase in FAK level of vagina tissue which is expressed mainly in epithelial basal layer. This study suggests that lncRNA 9708-1 played a protective role on murine experimental VVC by upregulating the expression levels of FAK.

Gentianella acuta prevents acute myocardial infarction induced by isoproterenol in rats via inhibition of galectin-3/TLR4/MyD88/NF-кB inflammatory signalling - Jia-Huan Sun; Hong-Xia Yang; Ting-Ting Yao; Yuan Li; Lin Ruan; Geng-Rui Xu; Chuang Zhang; Guo-Xin Guo; Ai-Ying Li (Inflammopharmacology, 2021)

Somatic embryogenesis in slash pine (Pinus elliottii Engelm): improving initiation of embryogenic tissues and maturation of somatic embryos - Fan Yang; Xin-Rui Xia; Xin Ke; Jianren Ye; Li-hua Zhu (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

The Role of 17β-Estrogen in Candida albicans Adhesion on Human Vaginal Epithelial Cells via FAK Phosphorylation - Ting Luan; Xia Liu; Pengyuan Mao; Xinyan Wang; Can Rui; Lina Yan; Yiquan Wang; Chong Fan; Ping Li; Xin Zeng (Mycopathologia, 2020)

Antioxidative and Probiotic Activities of Lactic Acid Bacteria Isolated from Traditional Artisanal Milk Cheese from Northeast China - Yunjia Shi; Xingyang Cui; Shanshan Gu; Xin Yan; Rui Li; Shuang Xia; Hongyan Chen; Junwei Ge (Probiotics and Antimicrobial Proteins, 2019)

ANKRD49 inhibits etoposide-induced intrinsic apoptosis of GC-1 cells by modulating NF-κB signaling - Xia Zhou; Wen-tao Wang; Jia Sun; Hong-yan Liu; Xin-yan Bai; Juan-juan Liu; Bao-feng Yu; Rui Guo; Hai-long Wang (Molecular and Cellular Biochemistry, 2019)

Isolation and purification of diterpenoids from the aerial parts of Isodon excisoides target-guided by UPLC-LTQ-Orbitrap-MS - Li-Ping Dai; Ling-Xia Zhang; Ya-Lin Liu; Hong Wu; Rui-Xin Liu; Meng Zhao; Shuang-Shuang Tian; Xue Jiang; Sui-Qing Chen (Natural Product Research, 2018)

Inhibition of P2X7 Receptor Ameliorates Nuclear Factor-Kappa B Mediated Neuroinflammation Induced by Status Epilepticus in Rat Hippocampus - Cheng Huang; Xiao-sa Chi; Rui Li; Xin Hu; Hai-xia Xu; Jin-mei Li; Dong Zhou (Journal of Molecular Neuroscience, 2017)

Puerarin may protect against Schwann cell damage induced by glucose fluctuation - Bing Xue; Lin Wang; Zhe Zhang; Rui Wang; Xin-xin Xia; Ping-ping Han; Li-jun Cao; Yong-hui Liu; Lian-qing Sun (Journal of Natural Medicines, 2017)

Glycyrrhizin inhibits porcine epidemic diarrhea virus infection and attenuates the proinflammatory responses by inhibition of high mobility group box-1 protein - Chang-chao Huan; Hua-xia Wang; Xiang-xiang Sheng; Rui Wang; Xin Wang; Xiang Mao (Archives of Virology, 2017)

Norovirus outbreaks in Fengtai District, Beijing, China, 2014 - Jin-Song Li; Meng Qin; Xiao-Gen Dong; Jun-Yong Yang; Xiao-Xin Yang; Xiu-xia Wei; Zhao-e Wang; Hui-ru Feng; Qin-rui Wu; Ruo-xi Li; Jie Li; Zhao-Jun Duan (Archives of Virology, 2016)

Cognitive-enhancing effects of hydrolysate of polygalasaponin in SAMP8 mice - Pan Xu; Shu-ping Xu; Ke-zhu Wang; Cong Lu; Hong-xia Zhang; Rui-le Pan; Chang Qi; Yan-yan Yang; Ying-hui Li; Xin-min Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

Variations of Nutrients in Gross Rainfall, Stemflow, and Throughfall Within Revegetated Desert Ecosystems - Ya-feng Zhang; Xin-ping Wang; Yan-xia Pan; Rui Hu (Water, Air, & Soil Pollution, 2016)

Association between the MTHFR A1298C polymorphism and risk of cancer: evidence from 265 case–control studies - Xin-Li Zhu; Zhi-Zhong Liu; Sen-Xiang Yan; Wei Wang; Rui-Xia Chang; Chun-Yan Zhang; Yan Guo (Molecular Genetics and Genomics, 2016)

Comparison of diurnal dynamics in evaporation rate between bare soil and moss-crusted soil within a revegetated desert ecosystem of northwestern China - Ya-Feng Zhang; Xin-Ping Wang; Yan-Xia Pan; Rui Hu (Journal of Earth System Science, 2016)

Dependence of shrub canopy water storage on raindrop size in revegetated desert - Xin-ping Wang; Hao Zhang; Ya-feng Zhang; Rui Hu; Yan-xia Pan (Hydrological Sciences Journal, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Potential impact of climate change on future water demand in Yulin city, Northwest China - Wang Xiao-jun; Zhang Jian-yun; Shahid Shamsuddin; He Rui-min; Xia Xing-hui; Mou Xin-li (Mitigation and Adaptation Strategies for Global Change, 2015)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

The influence of Caragana korshinskii shrub on soil and hydrological properties in a revegetation-stabilized desert ecosystem - Yan-Xia Pan; Xin-Ping Wang; Xin-Rong Li; Ya-Feng Zhang; Rui Hu; Hao Zhang (Hydrological Sciences Journal, 2014)

Condensation of water vapour on moss-dominated biological soil crust, NW China - XIN-PING WANG; YAN-XIA PAN; RUI HU; YA-FENG ZHANG; HAO ZHANG (Journal of Earth System Science, 2014)

Heterogeneity of soil surface temperature induced by xerophytic shrub in a revegetated desert ecosystem, northwestern China - YA-FENG ZHANG; XIN-PING WANG; YAN-XIA PAN; RUI HU; HAO ZHANG (Journal of Earth System Science, 2013)

Diurnal and seasonal variations of surface albedo in a spring wheat field of arid lands of Northwestern China - Ya-feng Zhang; Xin-ping Wang; Yan-xia Pan; Rui Hu (International Journal of Biometeorology, 2013)

A Compartment Model for the Membrane-Coated Fiber Technique Used for Determining the Absorption Parameters of Chemicals into Lipophilic Membranes - Xin-Rui Xia; Ronald E. Baynes; Nancy A. Monteiro-Riviere; Jim E. Riviere (Pharmaceutical Research, 2004)

A Novel in-Vitro Technique for Studying Percutaneous Permeation with a Membrane-Coated Fiber and Gas Chromatography/Mass Spectrometry: Part I. Performances of the Technique and Determination of the Permeation Rates and Partition Coefficients of Chemical Mixtures - Xin-Rui Xia; Ronald E. Baynes; Nancy A. Monteiro-Riviere; Ross B. Leidy; Damian Shea; Jim E. Riviere (Pharmaceutical Research, 2003)

A Simplified Liquid-Solid Extraction Technique for the Analyses of Pesticide Residues in Soil Samples - Xin-Rui Xia; Ross B. Leidy (Environmental Monitoring and Assessment, 2002)